Between the headlines of the Israeli - Arabic conflict: the coverage of CNN and Al Jazeera (2015)
The purpose of this article is to analyze the coverage made by CNN and Al Jazeera (in Arabic) to operation Caste Lead and the Goldstone Report during 2008 and 2009. This investigation is based in the theory of Qualitative Analysis of Content, by Wildemuth and Zhang. The methodology follows up with the one proposed by the authors in the main theory, complementing it with the Gamson and Modigliani´s Framing theory. The methodology mention above display the different in the coverage development, determined by the geopolitical influences; being CNN more influenced by a Western pro USA and pro Israeli speech, while Al Jazeera is more prone to support the Palestinian cause, this is the thesis of this article. During the development of the investigation, the thesis was demonstrated to be only partially accurate as CNN was not completely supportive to the Israeli arguments during the coverage, but Al Jazeera did have preferential speech for the Palestinian cause.